Glycoprotein isolated from eurycoma longifolia (Tongkat Ali) is capable of boosting testosterone levels in leydig cells - Jaya Vejayan, Palliah; Yasmin, A.C. Yahya; Sharifah A.T., Said; Aini Norhidayah, Mohamed; Venugopal, Jayarama Reddy; Normaiza, Z.; Halijah, Ibrahim (Faculty of Pharmacy, University of Benin, 2021)
Eurycoma longifolia (Tongkat Ali) is renowned for its aphrodisiac potential, and its active constituent has been presumed to be a protein and more likely a glycosylated protein. In this study, the ability of the glycoprotein to increase testosterone hormone levels was investigated. The dried root powder of the plant was extracted using water under reflux. The protein fraction was separated using size-exclusion chromatography and subjected to SDS-PAGE analysis. Thereafter the protein fraction was isolated from its glycoprotein using a lectin column. Finally, TM-3 Leydig cells were treated with the isolated glycoprotein fraction (50 µg/mL). The extraction yielded 14.3% w/w protein and the SDS PAGE analysis showed a single band at approximately 20 kDa. Treatment of TM-3 Leydig cells with the glycoprotein fraction for 72 hours demonstrated an increase in testosterone levels by almost 100% (0.36 ± 0.03 nmol/L) in comparison to the untreated cells (0.18 ± 0.05 nmol/L). The findings suggested that the glycoprotein in E. longifolia root can be easily isolated because its sugar moiety can bind to a lectin affinity column. Moreover, this glycoprotein was shown to have testosterone-boosting activity. These findings identified the glycoprotein as the bioactive constituent associated with its aphrodisiac properties.